The foundations of textual linguistics and the emergence of genres of discourse: theories and issues related to gender classification - Qahraman Sulaiman Ahmed (Zanco Journal of Humanity Sciences)
This article is a part of research in Language Sciences. It aims to highlight, on the one hand, theoretical data on the notion of textual genres and to demonstrate, on the other hand, the place and importance of the study of the notion of textual genres in modern linguistics. To do this, we will start this research with a theoretical overview followed by the question of textual genres which will lead us to better understanding the problems linked to their definition as well as to their classification around which many linguistic debates have been formed since these last two decades. From there, a study of textual analyzes seems essential to us. To sum up, there is a great necessity in unveiling the need for organization planning theories on a textual scale. Therefore, we will question the link between textual genre and linguistic features of texts.